STUDI TENTANG EKSISTENSI DALIHAN NATOLU DALAM PESTA MANGADATI MASYARAKAT BATAK TOBA DI KECAMATAN TUALANG KABUPATEN SIAK - Christine Mesri; Hambali Hambali; Ahmad Eddison (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research is motivated by community activities in the implementation of the traditional Mangadati tradition. The purpose of this study was to determine the existence of Dalihan Natolu in the Mangadati Party of the Toba Batak community in Tualang District. This study uses qualitative methods and data collection techniques that researchers do are observation, interviews and documentation. The Mangadati party is to make customs, implement, and preserve customs so that they always exist in the midst of society. Dalihan Natolu is the philosophy of life of the Toba Batak people in society which is taken from the function of the "three-legged furnace". This three-legged stove has long been used by the community for cooking. If one of its legs is missing or broken then the stove cannot be used, or the stove is not sturdy, and strong enough to hold a pan or pot of water. An image is made of that hula-hula, dongan tubu, and boru who do not communicate are like Dalihan Natolu who lost a leg who has no function in society and his family. Because of the function of the three-legged stove, the Dalihan Natolu philosophy was created as a guide for the Toba Batak community in socializing, greeting and binding kinship between clans. Tualang District is an overseas area for the Toba Batak people, therefore the community agrees to assimilate Dalihan Natolu for the realization of the party, without the constraints of distance, time, and economy. The agreement that Dalihan Natolu elements can be represented by clans in the area. Based on the results of the study, it can be concluded that the existence of Dalihan Natolu in the Mangadati Party of the Toba Batak community in Tualang District is still maintained with adjustments, namely Dalihan Natolu remains in the Mangadati Party, but based on mutual agreement, if the biological family is constrained attending the party then it is represented by the clan in the District. Tualang. Although it shifts the customary rules, this is a solution for the local community in order to keep the tradition going.Key Words : Existence, Community Of Batak Toba, Mangadati Party.